Acoustic attenuation performance of a round silencer with the spiral duct at the inlet - Łapka, Wojciech (Archives of Acoustics, 2007)
The acoustic attenuation performance of a round silencer with the spiral duct at the inlet is investigated. A Finite Element Method was used for a three-dimensional numerical computations in a COMSOL Multiphysics application. A time-harmonic analysis without airflow was used for a frequency range from 10 Hz to 2 kHz. The results show that the spiral duct at the inlet can improve the acoustic attenuation performance of a round silencer. The sound attenuation depends on a spiral lead, an absorbing material and frequency. The transmission loss of investigated acoustic system with spiral ducts is related to an initial acoustic system with circular pipe. The results are shown as a growth of transmission loss ΔTL given by an insertion of the spiral ducts. A specific parameter given by relation of the spiral lead s to constant circular duct diameter d is presented as s/d ratio. The value of ΔTL is determined by s/d ratio and increases in specific frequencies. An acoustic wave, in those frequencies, is there divided at the outlet of the spiral duct and major acoustic energy goes aside, directly to an absorptive material, and minor acoustic energy goes axially to the silencers outlet. This is the damping effect of the spiral ducts.